THE IMPACT OF USER INTERFACE AND TIME SCARCITY ON PURCHASE INTENTION THROUGH E-COMMERCE SHOPEE AMONG YOUNG ADULTS IN MANADO - Matthew Andrico Gerald Pattinaja Pattinaja; Marjam Mangantar; Merinda Pandowo (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2023)
The rapid development of technology and the internet has brought changes in views, concepts, and orientation in many fields including business and marketing. One of its proofs is that face-to-face business interaction has shifted into modern electronic based interaction called E-commerce. The form of research used in this study is using quantitative methods. And also using Simple Linear Regression. The results of this study show that there is a significant influence on the intention to purchase among young adults in e-commerce Shopee. And on the basis of this finding, it is concluded that user interface and time scarcity can determine the purchase intention of young adults in e-commerce. The results of the first hypothesis are accepted, meaning that user interface has a positive influence on young adults’ purchase intentions in Shopee. The results of the second hypothesis are accepted, meaning that time scarcity has a positive influence on young adults’ purchase intentions in Shopee. Therefore, it is advised that potential users and consumers be capable of fulfilling their financial comprehension and planning on spending based on limitations. The intention is for young individuals to avoid purchasing because of feelings that are sparked by profitable marketing in an effort to keep economic transaction activities stable.   Keywords: user interface, time scarcity, e-commerce, purchase intention